NATIONAL PLAN OF ACTION FOR MENTAL HEALTH AND PSYCHOSOCIAL RELIEF OF EARTHQUAKE SURVIVORS- EMERGENCY PHASE: National Plan of Action - Rana, Mowadat Hussain; Ali, Sohail; Yusufi, Babur; Shah, Farrukh S (Pakistan Armed Forces Medical Journal, 2006)
IntroductionImportance of Mental Health and Psychosocial Care for the Survivors of Disasters:On Saturday, October 8, 2005, a massive earthquake of 7.6 on Richter scale struck Azad Jammu and Kashmir and parts of the North Western Frontier Province of Pakistan. The estimates were of over 73,000 dead and more than 75000 severely injured. There were in excess of 2 million homeless and 4 million populations affected by the earthquake in one way or the other. This has been one of the biggest disasters in Pakistan for over 100 years.It is well known that following any disaster, survivors experience a number of emotional reactions. This is the result of the bodily changes that occur as a response to going through the disaster as well as the psychological reaction to the losses experienced by the individuals.The emotional reactions are mild during the initial period and affect almost all of the population. However about 20% experience sustained emotional reactions and these can become a serious handicap during the recovery and rehabilitation phases.(World Health Report, 2001).The main approach in dealing with the psychosocial fallout of disasters is by meeting the emotional needs through strengthening the personal / family and community coping skills and by emphasizing the “normalcy” of the emotional reactions. This can be done through sharing of skills, sharing of thoughts and feelings, listening to each other, relaxation and use of spiritual beliefs and practices. The second approach is to integrate emotional support, and psychosocial care, in all health contacts, through training of the health workers and doctors. The third measure is to rebuild the psychiatric services for treatment of those with pre-existing mental illnesses and those with severe emotional reactions to the earthquake.It was against this background of the recent earthquake and the recognition of the need for mental health/psychosocial care of the survivors, that the National Plan of action was developed to meet the needs of the survivors. There are two components to the Plan. The first part reviews and presents the broader framework for disaster mental health care and the second part presents an action plan. Indeed the plan was a dynamic and a flexible document and evolved in the light of the experiences gained. The Plan was able to accommodate the administrative as well as the socio-cultural variables.